Common garden test of range limits as predicted by a species distribution model in the annual plant Mimulus bicolor. Issue 6 (22nd June 2017) - Dixon, Andrea L.; Busch, Jeremiah W.
Abstract : PREMISE OF THE STUDY: Direct tests of a species distribution model (SDM) were used to evaluate the hypothesis that the northern and southern edges of Mimulus bicolor 's geographical range are limited by temperature and precipitation. METHODS: Climatic suitability was predicted using an SDM informed only by temperature and precipitation variables. These predictions were tested by growing plants in growth chambers with temperature and watering treatments informed by weather stations characteristic of environments at the geographic center, edges, and outside the range. An Aster analysis was used to assess whether treatments significantly affected lifetime flower production and to test for local adaptation. The relationship between climatic suitability and lifetime flower number in the growth chambers was also evaluated. KEY RESULTS: The temperature and watering treatments significantly affected lifetime flower number, although local adaptation was not detected. Flower production was significantly lower under the two edge treatments compared to the central treatment. While no flowers were produced under the beyond‐south treatments, flower production was greatest under the beyond‐north treatment. These results suggest a hard abiotic limit at the southern edge, and suitable temperature and precipitation conditions beyond the northern edge. While predicted climatic suitability was significantly lower at the range edges, there was no correlation between the climatic suitability of the weather stations' locations and flower production. CONCLUSIONS: These results suggest that temperature and precipitation play a significant role in defining the distribution of M. bicolor, but also indicate that dispersal limitation or metapopulation dynamics are likely important factors restricting access to habitable sites beyond the northern range limit.